Analisis Fatwa MUI No. 24 Tahun 2017 dalam Menjawab Tantangan Etika dan Transparansi Transaksi Virtual : Studi Kasus pada Platform E-Commerce Shopee dan Tokopedia (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2024)
This study examines the effectiveness of MUI Fatwa No. 24 of 2017 in addressing ethical and transparency challenges in virtual transactions, particularly on Shopee and Tokopedia platforms. Employing a qualitative descriptive-analytical method, the research utilizes primary sources, including the fatwa itself, and secondary literature from Islamic jurisprudence and academic publications. The findings highlight that while the fatwa provides substantial guidance on ensuring Sharia compliance in virtual transactions focusing on principles such as transparency, fairness, and the prohibition of gharar (uncertainty) and riba (usury) its practical implementation faces significant challenges. These challenges arise from the dynamic nature of digital commerce, including issues of unclear agreements, data security, and emerging financial technologies such as cryptocurrency. The study concludes with recommendations for refining and adapting Islamic legal rulings to align with technological advancements, ensuring that virtual transactions remain ethically and lawfully consistent with Sharia.